Age-Dependent Sex Hormone-Binding Globulin Expression in Male Rat. (April 2015) - Li, Yaqing; Li, Xiaoli; Fan, Huijie; Li, Xiaoran; Zhong, Yali; Cao, Jing; Yu, Dandan; Zhang, Mingzhi; Wen, Jian-Guo; Geng, Li; Suo, Zhenhe
Abstract Sex hormone binding globulin (SHBG) is known as a carrier protein, classically thought to be mainly synthesized in the liver and then secreted into the circulating system, where it binds to sex steroids with a high affinity and modulates the bioavailability of these hormones. In humans, the organs other than the liver known to produce SHBG include the brain, uterus, testis, prostate, breast and ovary, and the locally expressed SHBG is considered to play an important role in various physiological and pathological processes. A few studies of SHBG in rats were reported, but systemic SHBG studies in consideration of different organs and aging are currently missing. So we examined the SHBG expression in the brain, liver, prostate, and serum in 40 Sprague–Dawley male rats in four different groups (newborn, 2, 6, and 12 months old, respectively) with 10 in each group by immunohistochemistry, immunofluorescience microscopy, qRT-PCR, ELISA, western blotting, and laser confocal microscopy. We discovered that SHBG was increasingly expressed in all the three tissues along with age, and the SHBG protein expression was observed in the cytoplasm and membrane of neurons, hepatocyte, and prostate epithelial cells. The ELISA assay of the sera also supported an increasing SHBG level along with age. It is concluded that the locally synthesized SHBG in the liver, brain, and prostate and the circulating SHBG of male SD rats are positively associated with age, further indicating a potential role of SHBG in aging.